3D information visualization / N.F Mohd Noor and D. England - N.F ., Mohd Noor; D., England (2002)
In a World Wide Web, there are so many search engines that provide a list of query result according to the user keyword. User has to read line by line to search for the information they want. Some of the search engine result is confusing and unstructured. 3D information visualization allows a greater working volume for information presentation with focus, context and point of interest managed dynamically by the viewpoint. 3D graphics offer a greater level of flexibility for representing, organizing and presenting the information. With 3D information visualization, human experience in interacting and exploring within 3D environment is exploited. In this research the list of query result will be transformed into 3D information visualization to make easier for the user to find information from the web query. In order to test the effectiveness of the approach, an experiment was done to find out how fast the user get the information they want in 3D information visualization. The result showed an acceptable performance where in 3D information visualization, users working performance is increased.